Assessment of Knowledge and Attitude about Traumatic Dental Injuries First Aid of Faculty Members and Undergraduate Bachelor in Physical Education in the UP College of Human Kinetics of A.Y.2021-2022/ Mary Allyson B. Campos, Jeanne Louise S. de Paz and Kristina Patricia D. dela Rosa. - Campos, Mary Allyson B.; de Paz, Jeanne Louise S.; dela Rosa, Patricia D.; Mendoza, Michael Antonio F. (2022)
INTRODUCTION: Traumatic dental injury (TDI) is an injury of the hard and soft tissues
in the oral cavity by its collision with any object. Sports poses a greater risk of having
TDIs, necessitating a need for Physical Education and sports-related professionals to know
immediate measures after it happens in school and sports.
OBJECTIVES: The general objective of this study was to assess the knowledge and
attitude of faculty members and undergraduates of Bachelor in Physical Education (BPE)
at the University of the Philippines College of Human Kinetics (UP CHK) on TDIs First
Aid. Its correlation to certain demographic factors of the BPE faculty members and
undergraduates was also to be analyzed.
METHODS: The participants were faculty members and undergraduates of the BPE
program of the UP CHK in A.Y. 2021-2022. A cross-sectional analytical study design
through an online survey questionnaire was utilized. However, due to the high nonresponse
rate, the data collected was presented as individual case responses.
RESULTS: As the initial data collection resulted in a high nonresponse rate, a repeat of
the data collection was performed. Only 5 undergraduate students out of 250 and 0 faculty
members out of 29 responded. With the outcome, the projected data analysis could not be
employed. The knowledge of the 5 undergraduate students is inadequate in terms of
managing TDIs. Only 1 out of 5 respondents had adequate knowledge (scoring
≥70%), and 3 out of 5 respondents have an unfavorable attitude (scoring ≤ 2) towards
TDIs and its first aid.
CONCLUSION: The results of the study showed that the level of knowledge of the 5 BPE
undergraduate students regarding the management of TDIs is inadequate, while their
attitude showed a negative overall result. No significant association between the
demographic data and knowledge and attitude can be analyzed due to the high nonresponse
rate.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: First aid; Teeth -- Wounds and injuries